THE AFFECTION OF INTERVIEWER SUPPORT ON ONEÃ¢â¬â¢S PERCEPTION AND PERFORMANCE IN AN ORAL PROFICIENCY INTERVIEW - Pratama, Hendi (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2012)
This study examines the relationship of the support provided by the interviewers on the test-taker perception and performance. There are two levels of support investigated: High Supporting Behavior (HSB) and Low Supporting Behavior (LSB). Ten participants sat in two interviews with two different interviewers applying LSB and HSB condition each. All participants completed a perception questionnaire at the end of the interviews. Twenty interview scripts were computed to determine the participantsÃ¢â¬â¢ actual performance in three categories: (1) fluency, (2) lexical resources and (3) grammar complexity. The results of the study reveals that there are effects on performance but not perception.